2020
DOI: 10.1108/mrr-02-2020-0067
|View full text |Cite
|
Sign up to set email alerts
|

A cross-cultural study of the role of obstacles on resilience in leadership formation

Abstract: Purpose The paper aims to report findings from research conducted that illustrates cross-cultural differences and similarities on the role obstacles, as defined by leadership antecedents, play in the levels of resilience found in leaders. While research has demonstrated a link between obstacles and the development of resilience in leadership, previous studies have not looked at whether this link exists across cultures and what differences or factors might affect this link. Design/methodology/approach The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Furthermore, while Howard and Irving (2014) established a link between resilience and leaders' self-differentiation), in their later study (2021), they concluded that this holds true in US and Indian samples but not among German leaders. A practitioner interested in, for example, the relationship between leader resilience and training or leader resilience and difficult experiences will find it difficult to understand why the results by Howard and Irving (2021) showed a significant relationship between leader resilience and courses and resilience and personal mistakes but no connection between leader resilience and degree education or leader resilience and crisis experience.…”
Section: Leader Resiliencementioning
confidence: 99%
“…Furthermore, while Howard and Irving (2014) established a link between resilience and leaders' self-differentiation), in their later study (2021), they concluded that this holds true in US and Indian samples but not among German leaders. A practitioner interested in, for example, the relationship between leader resilience and training or leader resilience and difficult experiences will find it difficult to understand why the results by Howard and Irving (2021) showed a significant relationship between leader resilience and courses and resilience and personal mistakes but no connection between leader resilience and degree education or leader resilience and crisis experience.…”
Section: Leader Resiliencementioning
confidence: 99%
“…Leadership that seeks to build collective values in the form of an organizational vision and mission focusing on individuals in their contribution to achieving the best results is effective leadership that will improve performance (Rockstuhl et al, 2023). One form of effective leadership is resilient leadership with performance-oriented strategic thinking, the ability to adapt to change, and emotional intelligence (Howard & Irving, 2021). The combination of transformational leadership style and transactional style is the forerunner of resilient leadership (Dartey-Baah, 2015).…”
Section: Introductionmentioning
confidence: 99%